2015
DOI: 10.1007/s00415-015-7866-5
|View full text |Cite
|
Sign up to set email alerts
|

Walking improvements with nabiximols in patients with multiple sclerosis

Abstract: Recently, nabiximols was approved as a treatment in MS spasticity. Data leading to approval and clinical use of nabiximols, although widely recognised, are based on subjective scales. Movement analysis procedures would obtain more detailed data about the impact on mobility. The aim of the study was to quantitatively assess the functional modification of gait patterns induced by nabiximols in MS. We evaluated three-dimensional gait analysis (spatial-temporal and kinematic) variation by means of one-way ANOVA. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 25 publications
0
7
1
1
Order By: Relevance
“…It has been confirmed that motor dysfunction is a crucial problem in patients with MS ( Coghe et al, 2015 ). CUP mouse model shows severe motor dysfunction ( Li et al, 2015 ) and schizophrenia-like activity ( Liu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 95%
“…It has been confirmed that motor dysfunction is a crucial problem in patients with MS ( Coghe et al, 2015 ). CUP mouse model shows severe motor dysfunction ( Li et al, 2015 ) and schizophrenia-like activity ( Liu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 95%
“…It has been confirmed that motor dysfunction is a crucial problem in patient with MS (Coghe et al ., ), and CPZ model mice have severe motor dysfunction (Franco‐Pons et al ., ; Hibbits et al ., ; Li et al ., ), an impairment of spatial working memory ( Xiao et al ., ; Adilijiang et al ., ), and a diminishing of social interaction (Brunet‐Gouet & Decety, ). Recently, Lewis rats fed with CPZ exhibited demyelination and behavioral changes that are similar to white matter abnormalities observed in humans (Serra‐de‐Oliveria et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the growing number of studies involving the neuroprotective and immunosuppressive effects of CBD, the majority of human studies involving cannabinoids and MS have been focused on the use of THC:CBD mixtures, with a particular focus on Sativex. Clinical studies that have been performed have shown that Sativex has beneficial effects on spasticity, mobility, bladder function, and pain in MS patients, and is well tolerated 22,25,28,31,[168][169][170][171][172][173][174][175] ; however, there has been little focus on the neuroprotective and immunosuppressive effects of THC:CBD mixtures in MS, and so it is difficult to say at this point if the successful results observed with CBD in the animal models of MS will be observed in MS patients. For a more complete review on the effects of Sativex in MS, see Zettl et al 176 Other autoimmune disease states CBD has been shown to attenuate experimental autoimmune hepatitis, 86 experimental autoimmune myocarditis, 126 and autoimmune diabetes 123,124 in mice.…”
Section: Nichols and Kaplanmentioning
confidence: 99%